1990
DOI: 10.1152/ajpcell.1990.258.3.c524
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between myosin phosphorylation and shortening velocity in canine trachea

Abstract: The relationship between glycogen phosphorylase activity (an index of cytosolic Ca2+ content), myosin light-chain phosphorylation, isotonic shortening velocity, and isometric tension was examined in canine trachealis. Responses were measured in tracheal strips contracted with various concentrations of methacholine or K+. Both agonists produced prolonged and concentration-dependent increases in isometric tension that reached 90% of the plateau level within 1 (methacholine) to 5 (K+) min and remained stable over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…A transient increase in MLC phosphorylation is observed in association with a transient increase in shortening velocity during the maximal activation of rabbit trachealis muscle by muscarinic stimuli [115,125]; however, under many other conditions of stimulation, this correlation breaks down. Canine trachealis muscle activated by potassium (K + )-depolarization exhibits a decline in shortening velocity during the course of the contraction while high levels of active tension and myosin light chain phosphorylation are sustained [126,127]. A similar dissociation between shortening velocity and MLC phosphorylation is observed when trachealis muscles are activated with submaximal concentrations of muscarinic agonists or with agonists of lower efficacy, such as 5-hydroxytryptamine [126,128].…”
Section: Molecular Basis For the Mechanical Properties Of Tracheal Smmentioning
confidence: 98%
See 1 more Smart Citation
“…A transient increase in MLC phosphorylation is observed in association with a transient increase in shortening velocity during the maximal activation of rabbit trachealis muscle by muscarinic stimuli [115,125]; however, under many other conditions of stimulation, this correlation breaks down. Canine trachealis muscle activated by potassium (K + )-depolarization exhibits a decline in shortening velocity during the course of the contraction while high levels of active tension and myosin light chain phosphorylation are sustained [126,127]. A similar dissociation between shortening velocity and MLC phosphorylation is observed when trachealis muscles are activated with submaximal concentrations of muscarinic agonists or with agonists of lower efficacy, such as 5-hydroxytryptamine [126,128].…”
Section: Molecular Basis For the Mechanical Properties Of Tracheal Smmentioning
confidence: 98%
“…Canine trachealis muscle activated by potassium (K + )-depolarization exhibits a decline in shortening velocity during the course of the contraction while high levels of active tension and myosin light chain phosphorylation are sustained [126,127]. A similar dissociation between shortening velocity and MLC phosphorylation is observed when trachealis muscles are activated with submaximal concentrations of muscarinic agonists or with agonists of lower efficacy, such as 5-hydroxytryptamine [126,128]. It is therefore unclear whether the decline in shortening velocity that occurs in airway muscle during a sustained contraction can be attributed to the dephosphorylation of attached crossbridges (latchbridges).…”
Section: Molecular Basis For the Mechanical Properties Of Tracheal Smmentioning
confidence: 99%
“…Many studies have suggested that the cross-bridge cycling rate is proportional to the amount of MLCK and the resulting LC 20 phosphorylation levels (64,65). However, this direct link remains controversial (66)(67)(68). Nonetheless, several studies have reported significant increases of MLCK expression in asthma and in models of asthma.…”
Section: Total Smmhc In Asthmamentioning
confidence: 99%
“…Our model of innate airway hyperresponsiveness behaved similarly in that increased contractility was also associated with a greater level of phosphorylation. However, the specific role of this increased phosphorylation to enhanced Fischer airway smooth muscle contractility remains unclear given that recent reports have disputed the association between LC 20 phosphorylation and rate of shortening (32,34).…”
Section: Physiological Significance Of Increased Lc 20 Phosphorylationmentioning
confidence: 99%